Polarårboken Glacier (Polarboken, 2018)
Keywords: Antarktis; geografi; glasiologi

Ice-rise stratigraphy reveals changes in surface mass balance over the last millennia in Dronning Maud Land - Goel, Vikram; Martín, Carlos; Matsuoka, Kenichi (Journal of Glaciology, 2018)
We use ice flow modelling to simulate the englacial stratigraphy of Blåskimen Island, an ice rise in Dronning Maud Land and elucidate the evolution of this data-sparse region. We apply a thermo-mechanically coupled Elmer/Ice model to a profile along flowlines and through the ice-rise summit, where surface mass balance (SMB), flow velocity and ice stratigraphy were recently measured. We conclude that: (i) the ice rise is presently thickening at a rate of 0.5~0.6 m ice equivalent per year (mieq a−1), which is twice an earlier estimate using the field data and the input–output method; (ii) present thickening started 20–40 years in the past, before which the ice rise was in a steady state; (iii) SMB contrast between the upwind and downwind slopes was stronger than the present value by ~23% (or 0.15 mieq a−1) prior to ~1100 years ago. Since then, this contrast has been decreasing overall. We surmise that these SMB changes are likely a result of synoptic-scale atmospheric changes, rather than local atmospheric changes controlled by local ice topography. Our technique effectively assimilates geophysical data, avoiding the complexity of ice flow beneath the ice divide. Thus, it could be applied to other ice rises to elucidate the recent glacial retreat.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf